A review of concurrency control technique in distributed database - Kasim, Shahreen; Sinnasamy, Surain R.; Wui, Xiang Chiam; Cha, Pei Fong; Eng, Kong Yeoh; Wahid, Norfaradilla; Hafit, Hanayanti (Penerbit UTM Press, 2018)
Concurrency is a process where multiple simultaneous transactions of data in database system perform. Due to this condition, the concurrency control method can help and avoid the data inconsistencies when the system is accessed by the user. This paper elaborately discusses the distributed database in the aspect of concurrency control techniques. This research reviews three algorithms; DSL, VGA, and SBA in terms of the waiting time, validation, performance, delay and also the number of message exchange. SBA shows the best performance among others. Meanwhile, a comparison between FBS and S2PL be done in order to measure the time of response in high and low-security level. In Addition, the fairness level of the system also been measured. It is shown that FBS shows an improving of time and positive result when dealing with a high-security level performance of the transaction. FBS also improved in terms of fairness at the different level of security.